Antiulcer effect of lyophilized hydroalcoholic extract of Bixa orellana (annatto) leaves in rats - Huamán, Oscar (2009)
Objective: To identify the secondary metabolites present in Bixa orellana leaves extract, to evaluate the extract protection against ethanol injury, and histopathology study of the stomach glandular region. Design: Prospective, experimental and analytical research. Setting: Biochemistry and Nutrition Research Center laboratories, Universidad Nacional Mayor de San Marcos. Biological material: Bixa orellana leaves extract and male albino rats. Interventions: Secondary metabolites from the extract were analyzed using identification chemical tests. For evaluation of the gastro-protective effect proposed by Robert 1979 the extract was used at 200 and 400 mg/kg doses, and for macroscopic evaluation Marhuenda scale was employed. Tissues were preserved in 10% formaldehyde for histopathology examination by hematoxylineosin staining. Main outcome measures: Gastric lesions inhibition. Results: Bixa orellana leaves hydroalcoholic extract has phenolic compounds such as flavonoids and tannins, terpenes and alkaloids. Treatment with 200 and 400 mg/kg extract doses produced gastric lesions inhibition in respectively 21,7% and 28,3% (p<0,01). By histology, there was bigger protection and reduced migration of proinflammatory cells in the groups receiving 200 and 400 mg/kg extract. Control groups and those receiving ranitidine showed considerable lesion degrees and increased proinflammatory cells migration. Conclusions: Bixa orellana leaves hydroalcoholic extract produced gastroprotective effect against injury with 96% ethanol at both macroscopic and microscopic levels.